The evolving landscape of systemic therapy for well-differentiated neuroendocrine tumors of the lung - Yao, James C (International journal of endocrine oncology, 2017)
James Yao*, MD, is professor and chairman of gastrointestinal medical oncology at the MD Anderson Cancer Center (TX, USA). He is the chair emeritus of the North American Neuroendocrine Tumor Society (NANETS). He has numerous awards including the American Society of Clinical Oncology Career Development Award 2003, and the Carcinoid Cancer Foundation Research Award 2006, MD Anderson Distinguished Alumni Award 2009, Irwin H. Krakoff Excellence in Clinical Research Award 2011, and The Murray Brennan Distinguished Lecturer, Memorial Sloan-Kettering Cancer Center, 2012. In 1995, Dr. Yao received his doctorate of medicine at Baylor College of Medicine (TX, USA). His credentials include board of certification in internal medicine (ABIM) in 1999 and board of certification in medical oncology (ABIM) in 2003. Dr. Yao has special interests in neuroendocrine tumors and gastric cancer and has authored over 100 manuscripts including practice-changing articles in and . He has also been a principal investigator in numerous investigator initiated and multicenter clinical studies. He led the development of everolimus in neuroendocrine tumors from first patient treated through FDA approval for pancreatic neuroendocrine tumors in 2011 and lung and gastrointestinal neuroendocrine tumors in 2016.